The Legal Implication of Political Defection on Nigeria's Democracy - Khalid Idris Nuhu (Sriwijaya Law Review, 2021)
The prevalence of cross-carpeting in Nigerian politics continues to threaten the consolidation of democracy in the country. It is strengthened by the proliferation of political parties devoid of entrenched ideology or political philosophy besides attaining political and economic powers. The unusually delayed justice in defection related matters sometimes occasioned by the pile of cases before the scanty judicial umpire in the country is another block of stumbling over. The technical approach of these umpires to cases of defection or constitutional matters may not be far from being a cloak on the wheel of justice. While the elected executives at the detriment of their electorates enjoyed the freedom of assembly and association in changing their political parties after the election, the exercise of the same right by the elected members of legislative houses are subjected to certain occurrences in justification or else vacate their seats on the pronouncement of their respective leaders in the house. This historical political menace persistently thrives in the country's fledgling democracy without adequate legal instruments for effective redress. Through the conceptual approach, the study reveals that the elected executives persistently swindle the mandate of their voters with impunity while the principal officers of the parliaments freely decide who remains or exits the house on the ground of defection. It is clear that the Nigerian Anti Defection Law is inadequate in the changing political landscape of the country. This paper recommends a law reform to affect some enactments, particularly in the Constitution whereby machinery for the vacation of a seat in the parliament after defection can be beyond the powers of the principal officers, which is necessary for the attainment of socio-political orders in the country.